Use of Tubular Retractor for Resection of Colloid Cysts: Single Surgeon Experience and Review of the Literature. Issue 5 (7th May 2019) - Eichberg, Daniel G; Buttrick, Simon S; Sharaf, Jake M; Snelling, Brian M; Shah, Ashish H; Ivan, Michael E; Komotar, Ricardo J
Abstract: BACKGROUND: Colloid cysts are challenging lesions to access. Various surgical approaches are utilized which all require brain retraction, creating focal pressure, local trauma, and potentially surgical morbidity. Recently, tubular retractors have been developed that reduce retraction pressure by distributing it radially. Such retractors may be beneficial in colloid cyst resection. OBJECTIVE: To retrospectively review a single neurosurgeon's case series, as well as the literature, to determine the efficacy and safety profile of transtubular colloid cyst resections. We also aim to describe our operative technique for this approach. METHODS: We conducted a retrospective review of colloid cyst resections using either ViewSite Brain Access System (Vycor Medical, Boca Raton, Florida) or BrainPath (NICO, Indianapolis, Indiana) tubular retractors performed by a single neurosurgeon from 2015 to 2017 (n = 10). A literature review was performed to find all published cases of transtubular colloid cyst resections. RESULTS: Gross total resection was achieved in all patients. Early neurologic deficit rate was 10% (n = 1), and permanent neurologic deficit rate was 0%. There were no postoperative seizures or venous injuries. Average hospital stay was 2.0 d. There was no evidence of recurrence at average follow-up length of 13.6 mo. A literature review demonstrated nine studies (n = 77) with an overall complication rate of 7.8%. CONCLUSION: Tubular retractors offer an attractive surgical corridor for colloid cyst resections, avoiding much of the morbidity of interhemispheric approaches, while minimizing damage to normal cortex. There were no permanent complications in our series of ten cases, and a literature review found a similarly benign safety profile.